The Effect of Auditor Experience, Independence, and Integrity on Audit Quality with Professional Ethics as Moderating Variable: Empirical Study at Public Accounting Firms in Palembang City, Indonesia - Anjelita, Dedek; Tripermata, Lukita; Anggraini , Leriza Desitama (Manunggal Halim Jaya, 2025)
This research aims to analyze the influence of the auditor's experience, independence, and integrity on audit quality with professional ethics as a moderating variable in the Public Accounting Firm (KAP) in the city of Palembang. The research method used is quantitative with data collection techniques through distributing questionnaires to the auditors of the iKAP. Of the 100 questionnaires distributed, a total of 30 questionnaires were returned and processed. iThe results of the research show that the auditor's experience, independence, and integrity do not have a significant influence on audit quality. However, professional ethics have a positive and significant influence on audit quality. iIn addition, professional ethics has not been proven to be able to strengthen or weaken the relationship between the auditor's experience, independence and integrity on audit quality. These findings indicate that although professional ethics are important in audit practice, other factors may be more dominant in determining audit quality. Therefore, it is necessary to strengthen policies and improve training and supervision for auditors in implementing professional ethics in order to improve audit quality.